Periodic solutions of autonomous systems with pulse influence in critical cases - Boichuk, О. A.; Chuiko, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain existence conditions and iterative schemes for constructing periodic solution of weakly nonlinear autonomous systems with pulse influence in critical cases.